(untitled) (Eurasian Research Bulletin, 2023)
The article is devoted to the study of the etiology and pathogenesis of the occurrence of emotional burnout syndrome in medical students. Among medical students, there are cases of emotional burnout syndrome, when students have to change their chosen profession in the future, face difficulties in communicating with patients, and in more severe cases, drive themselves to suicide. Identification of etiopathogenetic factors of emotional burnout syndrome plays an important role in the timely prevention of the disease, the development of preventive measures.